Valorization of Mexican prickly pear cladodes (Opuntia spp) as a source of antifungal compounds against phytopathogenic strains - Vicente Antonio Mirón-Mérida; Martha Angélica Pardo-Islas; Jorge Yañez-Fernández; Paulina Gutiérrez-Macías; Blanca Estela Barragán-Huerta (CyTA - Journal of Food)
Prickly pear cactus (Opuntia spp.) has been widely consumed in Mexico as an important source of nutrients in the diet. Older, larger, and fibrous cladodes lose commercial interest for human consumption, resulting in a by-product rich in different bioactive compounds. In this work, the optimization of a microwave pretreatment combined with a reflux extraction of antioxidants from Opuntia spp cladodes was performed. The optimal factors were the liquid/solid ratio (24 mL/g), ethanol percentage (25%), and microwave pre-treatment time (3.88 min), with a phenolic content, antioxidant activity, and extract yield of 33.47 g GA/kg, 259.66 µmol Trolox/g, and 4.16%, respectively. The design was validated with fit percentages between 90.14% and 97.80%. The optimized extract exhibited growth inhibition against Colletotrichum gloesosporioides (85.27%), Fusarium verticillioides (58.47%), and Helminthosporium sp (77.87%). Furthermore, gallic acid, protocatechuic acid, rutin, myricetin, isorhamnetin, sinapic acid, and kaempferol were identified in the extract.